Moderating effects of support policy on agricultural productivity - Siti Fatimah Ismail; Nur Ain Ayunni Sabri; Eni Noreni Mohamad Zain; Mohd Rosli Mohamad (International Business Information Management Association, 2013)
Economic indicators have long been recognized as an important indicator for agriculture productivity. Yet, measurements of this relationship are still scarce and not always reliable. The power of agriculture comes not only from physical capital and human capital effect but also from its potentially strong support policy effects on the rest of agriculture productivity. This paper presents a conceptual framework of the effects of economic indicators on agricultural productivity. As productivity is the main concern of this paper, the moderating role of support policy is emphasized in this conceptual model. The propose model is important to reveal the trend of output and input in agriculture as well as the determinants of agricultural growth in Malaysia and ASEAN countries. From the graphical trends, it is not possible to assess the contribution of inputs (capital, labour, fertilizer etc.) to the overall output. Proposition stated and model proposed in the paper can be tested in empirical study in various economic sectors.